2020
DOI: 10.1007/s11116-020-10129-5
|View full text |Cite
|
Sign up to set email alerts
|

Getting the best of both worlds: a framework for combining disaggregate travel survey data and aggregate mobile phone data for trip generation modelling

Abstract: Traditional approaches to travel behaviour modelling primarily rely on household travel survey data, which is expensive to collect, resulting in small sample sizes and infrequent updates. Furthermore, such data is prone to reporting errors which can lead to biased parameter estimates and subsequently incorrect predictions. On the other hand, mobile phone call detail records (CDRs), which report the timestamped locations of mobile communication events, have been successfully used in the context of generating tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Despite the fact that mobility data alone cannot predict future needs (Bwambale et al, 2020), they can show already compelling citizens needs, like transportation or health care facility allocation needs. Moreover, thanks to the capability of collecting mobile data at very high time frequency and space granularity and backward in time, the time evolution of the MFA can indeed show changes or ongoing trends or help to design policies or measure the effectiveness of policies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that mobility data alone cannot predict future needs (Bwambale et al, 2020), they can show already compelling citizens needs, like transportation or health care facility allocation needs. Moreover, thanks to the capability of collecting mobile data at very high time frequency and space granularity and backward in time, the time evolution of the MFA can indeed show changes or ongoing trends or help to design policies or measure the effectiveness of policies.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no prior studies have estimated mode choice models based solely on mobile phone network data. Bwambale et al (2020) demonstrated the feasibility of a joint modelling framework for mobile phone and survey data in the case of trip generation and commented on the potential to apply similar models in the context of mode choice. To describe how activity patterns changes over time and space, Diao et al ( 2016) estimated a model for participation in different activities based on a travel survey and then applied it on mobile phone data so that the extent and variation of participation in activities at different times and places could be illustrated for an entire city.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that mobility data alone cannot predict future needs, they can show already compelling citizens needs, like transportation or heathcare facility allocation needs and they represent well human behavior (Bwambale et al 2020). Moreover, thanks to the capability of collecting mobile data at very high time frequency and space granularity, the time evolution of the mobility patterns can indeed show changes or ongoing trends or help to measure policy effects like the COVID-19 containment measures.…”
Section: Introductionmentioning
confidence: 99%